Enhancing group decision making with interval valued fuzzy soft max–min method: an examination in manpower recruitment - Abdul Razak, Samsiah; Abdullah, Ini Imaina; Yahya, Nur Azila (UiTM Cawangan Perlis, 2024)
Maji et al. expanded on soft set theory by introducing fuzzy soft set theory, offering a versatile approach for tackling problems marked by uncertainty and fuzziness, while effectively modelling and representing data. The authors developed a matrix representation within this fuzzy soft set framework and explored various properties of these matrices. Despite this, existing applications of interval-valued fuzzy soft matrices in group decision-making often assume equal importance for all criteria, which fails to capture the true preferences of decision-makers. This study proposes a novel approach to group decision-making through the Interval Valued Fuzzy Soft Max-min Decision-Making Method (IVFSMmDM), which considers the varying importance of each criterion, followed by using the Fuzzy Soft Max-min decision-making technique to prioritize decisions. The integration of these methods provides a more accurate and practical decision-making framework. The effectiveness of IVFSMmDM is illustrated through a detailed numerical example in the context of manpower recruitment, involving the selection of 7 programmers for a software development organization’s team. The results indicate that Programmer 5 was chosen, achieving the highest-ranking value of (0.019, 0.021).This highlights the practical utility and effectiveness of the Interval Valued Fuzzy Soft Max-min Decision-Making Method in real-world decision-making scenarios.